Peran Perusahaan Jasa Tenaga Kerja Indonesia Dalam Meningkatkan Ekonomi Masyarakat Menurut Perspektif Ekonomi Syariah - Rois, Adib Khusnul; Santoso, Arif; Syukroni, Azid; Candrakusuma, Muslih (Musyarakah: Journal of Sharia Economic (MJSE), 2024)
Indonesian Employment Services Companies can play an important role in improving the community's economy, especially from a sharia economic perspective. From a sharia economic perspective, this is very important because investment in human resources is considered a better investment than investment in goods and capital. By improving the quality of the workforce, the Indonesian Employment Services Company can make a greater contribution in developing more productive economic sectors, such as the service and industrial sectors. By paying attention to these aspects, the Indonesian Employment Services Company can help build a more inclusive, fair and sustainable economy, which is in line with sharia economic goals. This research was conducted with the aim of, first. To find out the role of Private Indonesian Migrant Worker Placement Implementers in sending Indonesian Migrant Workers abroad which includes the recruitment process, provision, departure and working relationships with agents abroad. Second. To find out the role of the Indonesian Employment Services Company in improving the economy of the study community at the Mulia Laksana Sejahtera Limited Liability Company, Ponorogo Branch. The results of this research, first, are that Private Indonesian Worker Placement Implementers have an important role in providing employment opportunities through sending Indonesian Workers abroad. The Implementer of Private Indonesian Worker Placement is responsible for carrying out good recruitment, providing provision and training, ensuring safe and legal departure, as well as protecting and paying attention to the welfare of Indonesian Workers. Second, the mechanism for improving the community's economy through Indonesian workers can be carried out by prioritizing income and remittances for Indonesian workers obtained through work that is halal and in accordance with sharia principles. Returning Indonesian workers can strengthen the sharia economy with sharia businesses that will strengthen the halal sector and create jobs in accordance with sharia principles.